Interference of iron on soil boron determination with azomethine-H in acid solutions - Ferreira, Gilvan Barbosa; Fontes, Renildes Lúcio Ferreira; Venegas, Victor Hugo Alvarez; Fontes, Maurício Paulo Ferreira; Pereira, Juliana Maria Nogueira (Pesquisa Agropecuaria Brasileira, 2002)
The search for methods to extract boron for evaluation of soil fertility to recommend fertilizer application is important due to the low levels of boron and high levels of iron in most Brazilian soils. Extraction with hot water, the standard method, is a hard work method with operational difficulties. On the other hand, solutions of CaCl2 5 mmol/L and BaCl2.2H2O 5 mmol/L have been used successfully. The objective of this work was to test the efficiency of the thioglycolic acid as a remover of Fe interference in the dosage of B with azomethine-H, after extraction from soil with acid solutions (Mehlich-1, 50 and 100 mmol/L HCl). Dosage with azomethine-H, with and without thioglycolic acid, in soil extracts from eight Minas Gerais State soils and two Mato Grosso do Sul State soils was performed. The reference method was the extraction with 5 mmol/L BaCl2.2H2O in the microwave oven and azomethine-H dosage. The determination of B with azomethine-H in extracts originated from acid extractions undergoes strong interference of Fe. The addition of thioglycolic acid does not remove this interference. The color of the B-azomethine-H complex becomes less stable as thioglycolic acid is added.
Keywords: thioglycolic acid; solutions; soil analysis; soil fertility